A novel anatomy-based five-settlement method for endoscopic thyroid lobectomy and ipsilateral central compartment neck dissection via gasless unilateral axillary approach: a preliminary report - Ge, Jun-Na; Yu, Shi-Tong; Sun, Bai-Hui; Wei, Zhi-Gang; Zhang, Zhi-Cheng; Chen, Wei-Sheng; Li, Ting-Ting; Lei, Shang-Tong (Frontiers in Endocrinology, 2023)
Abstract Background Endoscopic thyroidectomy (ET) via gasless unilateral axillary (GUA) approach has been widely implemented world worldwide. Based on our concept of mesothyroid excision in open surgery, we proposed a novel anatomy-based five-settlement method in ET via the GUA approach. This preliminary report aimed to explore the efficacy and safety of this method in patients with papillary thyroid carcinoma (PTC). Methods PTC patients who underwent endoscopic ET and unilateral central compartment neck dissection (CCND) via GUA approach with the five-settlement method at the department of general surgery, Nanfang Hospital, Southern Medical University from March 2020 to December 2021 were retrospectively collected. The data included general clinicopathological characteristics, surgical information (including duration, complication, and clinicopathological features), hospital stay information, and other medical records was documented. Results In total, 521 patients underwent lobectomy and CCND under the GUA approach with the five-settlement method. The mean number of lymph nodes yielded (LNY), and positive lymph nodes (PLN) were 5.7±4.3 (range, 1-30) and 1.0±1.8 (range, 0-12), respectively. The incidence of transient RLN injury was 1.1%. Chyle leakage and Horner’s syndrome respectively occurred in one patient (0.2%). Five (0.9%) patients developed a hematoma. No severe complications or conversion to open surgery have occurred. Conclusion The five-settlement method could be implemented safely and efficiently in ET+CCND via the GUA approach in selected PTC patients.